Analisis CFD Aliran Dua-Fasa Uap Air pada Pipa Geothermal Horisontal - Kumolosari, Eli; Dinaryanto, Okto; Wibowo, Teguh; Setiabudi, Dedet Hermawan; Nugroho, Fajar; Pinandhita, Lazuardy Rahendra; Kurniawan, Freddy (Institut Teknologi Dirgantara Adisutjipto, 2025)
Two-phase flow is a phenomenon that often found in various devices and fields, one of which is in the geothermal system. Two-phase flow parameters that are important to study include flow patterns, pressure drop, and water holdup. This study used the CFD method to obtain data on flow patterns, pressure drop, and water holdup in steam-water flow in horizontal pipes. Validation studies were conducted to obtain appropriate settings. The superficial velocities of steam and water were varied from 6-30 m/s and 0.05-0.1 m/s respectively. The results showed that the CFD results were in accordance with the experiments. Visually, the observed flow patterns were stratified-wavy flow and mist flow. Furthermore, the pressure drop and water holdup values obtained increased along with the increase in the JW value.